Village-Owned Enterprises : Building partnerships or business competitions (International Journal of Psychosocial Rehabilitation, 2020)
Rural areas in Indonesia have gradually experienced better changes since the law on villages Number 06 of 2016 was implemented. This indication can be seen from several aspects in rural areas that have experienced improvements, such as aspects of village infrastructure. The village road that runs along the village path is used by the community to facilitate mobilization activities in and out of the village. Other public facilities, such as agricultural roads for crop distribution, are also the focus of improvements made by the village government to support food security. Another aspect is that empowerment and development programs for rural communities are part of the government's main concern in implementing human development in rural areas. Community economic empowerment based on the local potential of the village is one of the orientations of the government to advance the economy in rural areas, such as the development of tourism villages (Trisnawati, Wahyono, Wardoyo, & Malang, 2018) and home industry businesses (Raharjana, 2012).